Modified Graphitic Carbon Nitrides for Photocatalytic Hydrogen Evolution from Water Copolymers, Sensitizers and Nanoparticles - Striegler, Karl (BestMasters,, 2015)
Karl Striegler investigates novel materials for photocatalytic hydrogen evolution from water. Graphitic Carbon Nitrides are an interesting class of materials with a structure close to graphite. For overcoming certain limitations, the author used different approaches to functionalize the basic material. He deposited nanoparticles to enhance the catalytic activity and used copolymerization as well as sensitizing to increase the amount of harvested light.  Contents Water Splitting Graphitic Carbon Nitrides Photocatalytic Hydrogen Evolution from Water Material Characterization and Improvement Sensitizing Nanoparticle Deposition  Target Groups Researchers and students in the field of chemistry The Author Karl Striegler is a Ph.D. student at the Institute of Chemical Technology, research group Heterogeneous Catalysis of Prof. Dr. Roger Gläser, at the University of Leipzig.  .